The workload analysis for the mackarel cracker industry's workers uses the full-time equivalents method - Cut Ita Erliana; Subhan A. Gani; Amri; Faisal Akbar (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Kerupuk Ikan Tenggiri Cap Kuda Laut is one of the fish-based cracker industries. The industry is located at Pangkalan Brandan, North Sumatra, Indonesia. The fish-based cracker industry employs 15 workers and six workstations, which include fish processing stations, fish grinding stations, kneading stations, printing stations, frying stations and packing stations. According to the observations, there is an unequal division of worker, which can result in an inappropriate workload for the worker. This study aims to analyze workers' workloads as a basis for determining the optimal number of workers. The full-time equivalent (FTE) method simplifies the measurement of work by aligning the number of people required to complete a specific job with the hours of workload. The study's findings revealed that one worker at the grinding stations had an overload, three workers in fish processing, two workers in kneading, three workers in frying and printing had normal workloads. Also at the packaging station there are 3 workers with an underload